2021
DOI: 10.3390/atmos12121638
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Biomass Burning Organic Aerosol Atmospheric Evolution and Chemical Aging

Abstract: The changes in the concentration and composition of biomass-burning organic aerosol (OA) downwind of a major wildfire are simulated using the one-dimensional Lagrangian chemical transport model PMCAMx-Trj. A base case scenario is developed based on realistic fire-plume conditions and a series of sensitivity tests are performed to quantify the effects of different conditions and processes. Temperature, oxidant concentration and dilution rate all affect the evolution of biomass burning OA after its emission. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Previous studies have investigated the phase behavior of some types of atmospheric aerosol particles, such as mixtures of secondary organic aerosol with inorganic salts and mixtures of secondary organic aerosol with hydrocarbon-like organic aerosol. However, the phase behavior of primary BBOA remains understudied and unresolved. Models simulating the microphysics, chemical evolution, concentration, or radiative properties of wildfire smoke typically assume that BBOA comprises only a single phase. , On the other hand, Jahn et al identified that some sampled BBOA particles exhibited an organic shell coating an organic core using transmission electron microscopy images, with the caveat that the vacuum conditions required for this type of microscopy may affect the particle morphology. In addition, bulk-phase liquid tar condensates generated from high-temperature wood distillation were reported to have separated into a water-soluble and nonsoluble oily phase, , although it is not known whether phase separation would occur in particles containing this material after equilibration with ambient relative humidity (RH).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated the phase behavior of some types of atmospheric aerosol particles, such as mixtures of secondary organic aerosol with inorganic salts and mixtures of secondary organic aerosol with hydrocarbon-like organic aerosol. However, the phase behavior of primary BBOA remains understudied and unresolved. Models simulating the microphysics, chemical evolution, concentration, or radiative properties of wildfire smoke typically assume that BBOA comprises only a single phase. , On the other hand, Jahn et al identified that some sampled BBOA particles exhibited an organic shell coating an organic core using transmission electron microscopy images, with the caveat that the vacuum conditions required for this type of microscopy may affect the particle morphology. In addition, bulk-phase liquid tar condensates generated from high-temperature wood distillation were reported to have separated into a water-soluble and nonsoluble oily phase, , although it is not known whether phase separation would occur in particles containing this material after equilibration with ambient relative humidity (RH).…”
Section: Introductionmentioning
confidence: 99%
“…After emission the primary BBOA can partially evaporate and secondary BBOA can form on and in the primary BBOA. 48,58 A highly viscous BBOA, as observed here, could limit the rate of evaporation of primary BBOA and the formation rate of secondary BBOA. [103][104][105][106][107][108] A recent modelling study that investigated the evolution of BBOA by evaporation of primary BBOA and the formation of secondary BBOA assumed the BBOA was liquid-like with a diffusion coefficient of 10 -10 m 2 s -1 .…”
Section: Discussionmentioning
confidence: 63%
“…Current atmospheric models that treat biomass burning organic aerosols typically consider them as single-phased particles. 37,[47][48][49] The results herein show that BBOA, at least in regions where forests primarily consist of pine trees, should be treated as having two separate phases. Depending on the degree of internal/external mixing of organic aerosol in forest fire plumes, these two phases may coexist and be separated within individual particles.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, the phase behavior of primary BBOA remains understudied and unresolved. Models simulating the microphysics, chemical evolution, concentration or radiative properties of wildfire smoke typically assume that BBOA comprises only a single phase (24,(36)(37)(38). On the other hand, Jahn et al identified that some sampled BBOA particles exhibited an organic shell coating an organic core using transmission electron microscopy images (39), with the caveat that the vacuum conditions required for this type of microscopy may affect the particle morphology.…”
Section: Introductionmentioning
confidence: 99%